Inverse association between total testosterone concentrations, incident hypertension and blood pressure - Torkler, Sarah; Wallaschofski, Henri; Baumeister, Sebastian E.; Völzke, Henry; Dörr, Marcus; Felix, Stephan; Rettig, Rainer; Nauck, Matthias; Haring, Robin (The aging male, 2011)
Background. Studies on the relationship between testosterone concentrations and blood pressure have yielded inconsistent results. Therefore, this study investigated the prospective association of total testosterone (TT) concentrations with risk of incident hypertension and blood pressure change in 1484 men aged 20-79 years. Methods. Data from the population-based Study of Health in Pomerania, Germany, were used. Serum TT concentrations, measured by chemiluminescent enzyme immunoassays, were categorised into age-specific quartiles. Generalised Estimating Equation (GEE) models, adjusted for age, waist circumference, physical activity, smoking and alcohol consumption were specified. Results. During a median follow-up time of 5.0 years, the prevalence of hypertension increased from 50.6% to 57.1%. TT concentrations were significantly lower in men with baseline and incident hypertension. Analyses revealed that men with baseline TT concentrations in the lowest quartile had an increased risk of incident hypertension (odds ratio (OR), 1.19 (95% CI, 1.10-1.28)) compared to men with higher TT concentrations. Furthermore, we found a significant inverse association of TT concentrations and blood pressure, showing that men with baseline TT concentrations in the lowest quartile showed the slightest change in systolic blood pressure (−6.01 mmHg), diastolic blood pressure (−2.11 mmHg) and pulse pressure (−3.98 mmHg). Sensitivity analyses in a subpopulation of men without antihypertensive medication confirmed these findings. Conclusion. These results show that low male TT concentrations are predictive of hypertension, suggesting TT as a potential biomarker of increased cardiovascular risk.